SY44-4ALCOHOL USE DISORDER AND RELATED MEDICAL PROBLEMS IN A GENERAL HOSPITAL. (September 2014) - Ratta-apha, W.; Sitdhiraksa, N.; Pariwatcharakul, P.; Saisavoey, N.
Abstract : Introduction. Alcohol use disorder is the leading cause of years lost due to disability among Thai males in 2009. When assessed in disability-adjusted life years, it is ranked as the number one psychiatric disorder. Consequently, this makes alcohol-related problems very common in general medical settings. One of the most serious psychiatric conditions related to alcohol use disorder is alcohol withdrawal delirium, which is the focus this study. Methods. Medical records from a cohort of alcohol-dependent patients admitted in a general hospital between 2012-2013 were reviewed. The history of alcohol use, withdrawal symptoms, clinical and medical conditions of patients who developed alcohol withdrawal delirium were extracted and compared with those who did not. Results. As compared to the psychiatric inpatient unit, most of the alcohol-dependent patients admitted in the medical/ surgical inpatient units suffered from alcohol withdrawal delirium and showed more complications. We also found out that certain symptoms of alcohol withdrawal and laboratory parameters were predictive of the development of alcohol withdrawal delirium (detailed results will be presented during the symposium). Conclusions. Patients with alcohol dependence and alcohol withdrawal delirium are commonly associated with deteriorated physical health conditions. Hence, it is important to be aware of the risk factors and prevent or promptly treat alcohol withdrawal symptoms. On top of that, the set up an intra-hospital consultation-liaison system between psychiatric and other departments will definitely improve the overall care of these patients.